Poetyka doświadczenia Teoria - nowoczesność - literatura - Nycz, Ryszard (Nowa Humanistyka, 2012)
In Part I, Ryszard Nycz formulates an opinion on the topical specifics of the humanities' studies; the opinion is rooted in the traditions of the discipline (literary studies), the ability of its influential orientation (intertextual poetics), as well as the writings of T. W. Adorno, one of the most astute philosophers and researchers of modern culture. In Part II, the author drafts a modified formula for carrying out the theory of literature, the aim of which is to avoid not merely its marginalisation, but its breaking-up (and the assigning of it to anthropology and/or cultural studies in particular). In Part III, the author endeavours to delineate the tasks of literary criticism, exposed to challenges generated by the changes in the function and status of national literature, models of identity, and in the relationships between the global and local dimension of contemporary culture. In Part IV, case studies are used to critically test the traditional view of the solely-applied character of interpretation against theory. The last part, 'Literature: A Reading of a Letter', acts as a summary. In it, the author depicts a concept of literature precisely as poetics of experience, as well as drafting a sketch of the theory of its understanding. As part of this theory, in the entirety of the practices and procedures of getting to know it, the author distinguishes three separate (in some aspects) tasks: spontaneous understanding, intellectually rigorous interpretation, and the experience of reading.